Multilevel Governance dalam Penguatan Peluang Kerja dan Usaha di Kabupaten Lombok Timur, Nusa Tenggara Barat - Stera Triastuty; Lala Kolopaking; Djuara Lubis (Sodality: Jurnal Sosiologi Pedesaan, 2023)
The progress of development and tourism in East Lombok Regency results in a need for labour and demands the mindset of society to be able to keep up with changes. Institutions of local communities such as pesantren (Islamic boarding school) and non-formal educational institutions provide services to the community for increasing competence. The community encourages the society to play a role in filling job and business opportunities and maintaining local wisdom. Community activities attract other actors from various levels, both government and private, to offer collaboration as an instrument to achieve goals. The community’s expectation of collaboration is synergizing, not delegating bureaucratic affairs. This approach offers an inclusive and participatory relationship within the Multilevel Governance (MLG). This study uses a qualitative approach with a constructivism paradigm. Data collections was carried by observation, interview, and documentation. The aim of the research is to see how the community's expectations of the MLG approach are in strengthening job and business opportunities and how the community's SOAR strategy analysis maintains the sustainability. The results of the study show that the awareness of the actors in carrying out their roles and authorities creates a conducive environment for the community to be independent. The strategy SOAR analysis is in the OA quadrant, advantage of opportunities to achieve expectations by developing partnerships that create participatory dialogue to strengthen accessibility and support local potential